The Influence of Reciprocal Relationships and Trust on Sharia Cooperative Member Satisfaction - Khoirunisa; Risa Bhinekawati; Muhammad Najib (Sekolah Tinggi Ekonomi dan Perbankan Islam Mr. Sjafruddin Prawiranegara, 2023)
Cooperatives have a role as pillars of economic and social development of the community, but they still experience many internal and external challenges, including in managing the satisfaction of their members. This study answers these challenges through the application of Social Exchange Theory, with the aim of analyzing whether reciprocity and trust have influence on the satisfaction of cooperative members. The study gathered 200 respondents from nine sharia cooperatives in six provinces of Indonesia. Using multiple regression models, the collected data was tested and further analyzed using SPSS 24.0 Software. This research found that Reciprocity and Trust have a positive and significant influence on the Satisfaction of sharia cooperative members. This research provides empirical evidence for the application of Social Exchange Theory in explaining the factors influencing the satisfaction of cooperative members that was not studied before. Sharia cooperative management can apply the results of this research to improve cooperative performance by building mutually beneficial and trusting relationships with its members. The results of this study can be generalized to sharia cooperatives, while the application to conventional cooperatives needs to be further studied. Keywords: Reciprocity, Trust, Satisfaction, Shariah Cooperatives, Social Exchange Theory